A195 A RARE CAUSE OF SEVERE REFRACTORY DIARRHEA IN A PATIENT WITH COMMON VARIABLE IMMUNE DEFICIENCY ASSOCIATED INTESTINAL ENTEROPATHY - Markandey, B (J Can Assoc Gastroenterol, 2021)
BACKGROUND: CVID is the most common type of severe antibody deficiency. Gastrointestinal manifestations affect approximately 20–50% of patients. Boland et al. described in a case series that 2/3 CVID patients were able to achieve clinical and endoscopic remission with Vedolizumab. This α4β7 integrin antagonist inhibits intestinal T cell translocation by blocking integrin interactions with mucosal vascular addressin cell adhesion molecule 1, reducing lymphocyte mediated inflammation. However, despite its novel use for this indication, limited data is available on the consequences of this therapy in patients with CVID. AIMS: To report on a case assessing the efficacy and outcomes of Vedolizumab for the treatment of CVID associated autoimmune enteropathy. METHODS: We present the case of a 50-year-old male presenting with severe refractory diarrhea and malnutrition. A colonoscopy demonstrated patchy ulceration and biopsies revealed ulcerated active colitis, negative for CMV. He was treated with Vedolizumab and Total Parental Nutrition (TPN). His diarrhea resolved, he gained 20 kg and he was weaned off TPN. In 2019, he re-presented with severe diarrhea. Subsequently endoscopic evaluation revealed patchy edematous colonic mucosa and biopsies demonstrated minimally active colitis, negative for CMV. He again responded to Vedolizumab re-induction, however shortly after, his diarrhea returned aggressively. CT enterography demonstrated active jejunal inflammation. Subsequently, an EGD revealed multiple duodenal ulcers and luminal narrowing. Biopsies of the small bowel were sent to histopathology. RESULTS: CMV superinfection was diagnosed on pathology (image 1). This patient’s diarrhea completely resolved with IV Gancyclovir and he was discharged on maintenance treatment with oral Valganciclovir. CONCLUSIONS: This represents the first reported case of CMV enteritis secondary to Vedolizumab for the treatment of CVID associated autoimmune enteropathy. In this case, clinical and endoscopic remission was observed with Vedolizumab, however subsequently hampered by CMV reactivation. Hommel et al., published a positive correlation in a single centre retrospective cohort study of CMV reactivation in patients with ulcerative colitis treated with Vedolizumab. A large retrospective review of data from a multicenter consortium database of over 1000 Vedolizumab treated IBD patients reported CMV colitis in only 4 patients. CMV reactivation appears to be an exceptionally rare but important event in patients treated with Vedolizumab. Based on this report, patients with CVID associated enteropathy and refractory diarrhea should be carefully screened for CMV when treated with Vedolizumab. Further prospective data assessing the incidence of CMV reactivation in patients with Vedolizumab therapy is required to further define these findings. FUNDING AGENCIES: None